Hypertension in children (12-14 years)–a case-control study in Bursa, Turkey - Akiş, Nalan; Pala, Kayihan; Meriç-Utku, Arzu; Seyithan, Bingöl; Sarandöl, Emre; Aytekin, Hamdi (The Turkish Journal of Pediatrics, 2009)
The aim of this study was to determine the cardiovascular disease risk factors (risk of overweight/overweight, dyslipidemia, paraoxonase-1 activity, positive family history, physical inactivity, smoking) that accompany hypertension and investigate the relationship between hypertension and some of these risk factors. This study included 118 hypertensives and 118 age- and sex-matched non-hypertensive controls aged 12-14 years. Among controls, 64.4% had no risk factor. Among cases, 34.8% had no risk factor other than hypertension, and 65.2% had two or more risk factors. The adjusted odds ratio (OR) (95% confidence interval [CI]) of hypertension was 5.65 (2.88-11.09) for risk of overweight/overweight. Body mass index, paraoxonase and arylesterase activities were significantly higher in hypertensives than those of the control group. We conclude that it would be useful to routinely evaluate blood pressure and body weight at schools and, additionally, considering that hypertension alone is encountered rarely, it would be appropriate to examine the hypertensive students for other risk factors.